1995
DOI: 10.1128/jvi.69.11.7032-7044.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic analysis of human immunodeficiency virus type 1 Vpr: role of a predicted N-terminal alpha-helical structure in Vpr nuclear localization and virion incorporation

Abstract: The Vpr gene product of human immunodeficiency virus type 1 is a virion-associated protein that is important for efficient viral replication in nondividing cells such as macrophages. At the cellular level, Vpr is primarily localized in the nucleus when expressed in the absence of other viral proteins. Incorporation of Vpr into viral particles requires a determinant within the p6 domain of the Gag precursor polyprotein Pr55 gag. In the present study, we have used site-directed mutagenesis to identify a domain(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(124 citation statements)
references
References 46 publications
(68 reference statements)
5
117
2
Order By: Relevance
“…Mutation of Ala30 to leucine completely abolishes G 2 cell cycle arrest and virion packaging of Vpr [23]. Mutations of either Leu23 or Ala30 to phenylalanine dramatically reduce virion incorporation of Vpr but do not interfere with its nuclear localization [24]. One may speculate, that the leucinezipper like sequence motif preceding Ala30 serves together with helical secondary structure as a basis for a variety of protein±protein interactions between Vpr and other viral and cellular factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Ala30 to leucine completely abolishes G 2 cell cycle arrest and virion packaging of Vpr [23]. Mutations of either Leu23 or Ala30 to phenylalanine dramatically reduce virion incorporation of Vpr but do not interfere with its nuclear localization [24]. One may speculate, that the leucinezipper like sequence motif preceding Ala30 serves together with helical secondary structure as a basis for a variety of protein±protein interactions between Vpr and other viral and cellular factors.…”
Section: Discussionmentioning
confidence: 99%
“…The various isogenic proviral type or mutant Env and the G glycoprotein of VSV. In order to ensure that VSV-G is incorporated in HIV virions even in the presence of Env, constructs were obtained as follows: vprϩ/-: HxBRU and HxBRURwith a stop codon at the initiation site of the vpr gene of HIV-BRU 10 6 COS cells were transfected with 10 μg of either proviral construct with or without 10 μg of SVCMV-VSV-G by the lipofection method have been described elsewhere (Lavallée et al, 1994;Yao et al, 1995); vpuϩ/-: HXBH10 and HXBH10vpu-, were described previously (Yao (Leventis and Silvius, 1990;Mouland et al, 1994). Cells were labeled 40 h after transfection with 150 μCi/ml of [ 35 S]methionine for 8 h. et al, 1992); nefϩ/-: pNL4.3-based pNLV102 and pNLV102ΔXho, gifts of Dr S.Venkatesan, and described previously (Ahmad and Venkatesan, Supernatants were harvested and ultracentrifuged (30 000 r.p.m.…”
Section: Incorporation Of Vsv-g In Hiv Virionsmentioning
confidence: 99%
“…Although numerous studies have demonstrated that HIV‐1 Vpr mutations could dramatically affect its known functions , these mutations were generated in the lab and did not represent the profile of the naturally occurring mutations over the course of infection. Indeed, in order to address the correlation between the structural domains and Vpr function, a set of molecular strategies involving deletion, insertion and/or substitution mutagenesis was developed.…”
Section: Vpr Mutations‐dependent Phenotypesmentioning
confidence: 99%
“…Nevertheless, it should also be considered that it may be easy to disrupt the interactions of Vpr by disrupting its structure, because it is a relatively small protein. The tertiary structure of Vpr was determined by Morellet and colleagues (2003), who performed a nuclear magnetic resonance analysis of the full‐length polypeptide . Vpr contains three α‐helical domains with amphipathic properties, linked by loops and folded around a hydrophobic core surrounded by a flexible N‐terminal domain and a C‐terminal arginine‐rich region that are negatively and positively charged, respectively (Figure ).…”
Section: Introductionmentioning
confidence: 99%